Case Report: Exercise-Induced Supraventricular Tachycardia in a 16-Year-Old Boy with Tricuspid Regurgitation - Putu Satya Pratiwi; Romy Windiyanto (WMJ (Warmadewa Medical Journal), 2020)
Supraventricular tachycardia (SVT) is a tachydysrhythmia that is often found in pediatric patients which requires treatment. In contrast to sinus tachycardia, SVT is not a normal compensatory response to physiologi-cal stress. This article discusses the case of supraventricular tachycardia in a 16-year-old boy, which appear during strenuous exercise. In this case a guide was also provided in identifying SVT, excluding the differential diagnosis for narrow complex tachycardia, followed by guidelines for the management of pediatric tachycardia based on the Pediatric Advanced Life Support algorithm.